The needed competencies to activate School Theater from the prospective of school activities operators in Jeddah directorate of education - Alsahafi, Sarah Saleh Ahmad; Al- Badi, Nouf Mohammed (Journal of Educational and Psychological Sciences, 2021)
The study aimed to: Identify the concept of the basic competencies of school theater from the point of view of those in charge of the school theater (women teachers, supervisors and leader of student activity in the education of Jeddah, also to Identify the basic competencies that frame the concept of school theater according to Vision 2030, to learn about the challenges that impede the application of school theater in the educational field, finally knowing the future of school theater according to Vision 2030. The study used the qualitative approach to be the methods used in the study. Population of the study consisted of leader, supervisors of the activity and women teachers of girls ’education schools. The study sample amounted 21 educational supervisors from 4 offices in the Education Department in Jeddah. Important results came as the follows: The presence of the appropriate theatrical text is one of the most important competencies that must be provided to be activated, indicated to some challenges that hindered its development, such as low awareness, , its also mentioned the factors that will affect it in the future, as it recommended the need to raise awareness and provide Theaters equipped to activate theatrical movement, and adopting it as a subject within the educational curriculum, and it has its own teacher.
Keywords: necessary sufficiency; school theater; theatrical activity; education management